Emotional Violence Caused by the Effect of Parents’ Role in Cultural Hegemony of Social Control on Children in Lia Shine’s TerpaksaMenikah: A Case Study - Putra Pratama Saputra (Faculty of Social and Political Sciences University of Bangka Belitung, 2018)
Emotional violence is violence that can frustrate social development on children or mental health children. Emotional violence is verbal violencethat is usually received by the involving feelings in himself. This will impact that distasteful to the development of children. According to Moffat âemotional violence will make children unable to give or receive affection normallyâ. Research has a reference to see hegemony cultural influenced by violence emotional, where hegemony culture is an aspect of leadership where it is dominated by a class that cause a pressure in the domain of the habit or culture. This relatively relation to social control in emotional children. So it will be examined through the theory of social control which will show expectation of violent emotional to the development of children.